2021
DOI: 10.1039/d1fo00208b
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with Bacillus subtilis and xylo-oligosaccharides improves growth performance and intestinal morphology and alters intestinal microbiota and metabolites in weaned piglets

Abstract: The present study was conducted to investigate the effects of dietary supplementation with Bacillus subtilis (BS) and xylo-oligosaccharides (XOS) on growth performance, intestinal morphology, intestinal microbial community, and metabolites of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Firmicutes, Bacteroidetes, Proteobacteria , and Actinobacteria were the most abundant phyla in the ileum and colon of piglets at the phylum level, as these phyla are the predominant in the swine gastrointestinal tract ( 27 , 28 ). Meanwhile, Firmicutes abundance was increased and Bacteroidetes was decreased in the ileum and colon of piglets after the FCR supplementation in piglet's diet.…”
Section: Discussionmentioning
confidence: 99%
“…Firmicutes, Bacteroidetes, Proteobacteria , and Actinobacteria were the most abundant phyla in the ileum and colon of piglets at the phylum level, as these phyla are the predominant in the swine gastrointestinal tract ( 27 , 28 ). Meanwhile, Firmicutes abundance was increased and Bacteroidetes was decreased in the ileum and colon of piglets after the FCR supplementation in piglet's diet.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a dietary supplementation with 400 mg/kg XOS also increased final BW and ADG in nursery pigs, while ADFI and FCR were not affected ( 12 ). Additionally, a dietary supplementation of 250 mg/kg XOS markedly increased ADG and ADFI for weaning piglets ( 25 ). The difference between our findings and previous reports might be attributable to the dosage of XOS.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some bacterial species of the intestinal microbiota of IUGR pig, such as Lactobacillus , showed a negative correlation with the growth performance, while Unclassified _ Ruminococcaceae was positively correlated [ 5 ]. Colon harbors the largest concentration of bacteria in mammals, including pigs, and these bacteria produce a variety of metabolites, which play an important role in the host physiology and pathophysiology, notably in the large intestine [ 6 ], but also in the development of metabolic disease [ 7 ]. Recent studies showed that IUGR altered several bacterial metabolites with known biological activities, including short-chain fatty acids, bile acid derivatives, and indole derivatives [ 8 ].…”
Section: Introductionmentioning
confidence: 99%